The crucial role of entrepreneurship education at university using different educational practices - Damrath, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
In 2020, the world was unexpectedly struck by the coronavirus pandemic. Regulations introduced by the governments have affected many businesses. The key problem is a good preparation of entrepreneurs for similar crises. One of the main factors influencing entrepreneurial activities is entrepreneurship education, mainly at the university level. The article aims to analyse different education practices focused on learning entrepreneurship, especially at universities, in selected countries. The work is analytical and descriptive.
Keywords: entrepreneurship; education; students; universities; government policy